PENGARUH PROGRAM PENGENTASAN KEMISKINAN DI 25 PROVINSI WILAYAH PRIORITAS PENGENTASAN KEMISKINAN EKSTREM - Anindita, Gabriella Natalie Krista; Nurhayati (Media Ekonomi, 2024)
The purpose of this research is to analyze the influence of poverty alleviation programs of 25 provinces in Indonesia as part of the priority areas for eradicating extreme poverty stage II in 2020 – 2023 period.  This research uses panel data regression methods to determine the effect of poverty alleviation programs, namely the Program Keluarga Harapan (PKH), Bantuan Pangan Non-Tunai (BPNT), Kartu Prakerja (KPK), and Kredit Usaha Rakyat (KUR) on poverty levels. Secondary data of 25 provinces in Indonesia as part of the priority areas for eradicating extreme poverty stage II in the 2020 – 2023 period was obtained from the Central Statistics Agency (BPS), the National Team for the Acceleration of Poverty Reduction (TNP2K), and other ministries/institutions. The regression results show that KUR has a negative effect on poverty levels, while PKH, BPNT, and KPK have no effect on poverty levels in 25 provinces in Indonesia as part of the priority areas for eradicating extreme poverty stage II in the 2020 – 2023 period